Chirality-independent characteristic crystal length in carbon nanotube textiles measured by Raman spectroscopy. (May 2017) - Bulmer, John S.; Gspann, Thurid S.; Barnard, Jon S.; Elliott, James A.
Abstract: Raman spectroscopy's D:G ratio is a well-known indicator of graphitic crystallinity in single-wall carbon nanotubes (SWCNTs) with widespread qualitative application to macroscopic CNT assemblies. Here, we show how the D:G ratio yields quantitative characteristic crystal length features that is remarkably independent of SWCNT chirality when purified SWCNTs are in a high density, heavily bundled textile form. Purified, unaligned, SWCNT films of enriched length distributions and controlled chirality responded in ways consistent with power law behaviour, where the D:G ratio is proportional to the fourth power of excitation wavelength, inversely proportional to SWCNT length, and fits to a master curve independent of electronic species concentration. This behaviour, matching the established response of graphite and graphene, unexpectedly persists despite complications from chirality-dependent resonances unique to SWCNTs. We also show that textiles comprising of aligned, long length CNTs defy these simple power laws until defective multiwall CNTs and impurities are removed post-process, and only if sample heating under the Raman laser is minimized. Adjusting the Raman laser beam diameter up to 6 mm, which is well beyond the average CNT length, we propose that the CNT textile's characteristic crystal length is the CNT length or, with point defects, the distance between point defects. Graphical abstract: